Disparate rates of acute rejection and donor‐specific antibodies among high‐immunologic risk renal transplant subgroups receiving antithymocyte globulin induction. (7th July 2016) - Patel, Samir J.; Suki, Wadi N.; Loucks‐DeVos, Jennifer; Graviss, Edward A.; Nguyen, Duc T.; Knight, Richard J.; Kuten, Samantha A.; Moore, Linda W.; Teeter, Larry D.; Gaber, Lillian W.; Gaber, A. Osama
Summary: Lymphocyte‐depleting induction lowers acute rejection (AR) rates among high‐immunologic risk (HIR) renal transplant recipients, including African Americans (AAs), retransplants, and the sensitized. It is unclear whether different HIR subgroups experience similarly low rates of AR. We aimed to describe the incidence of AR and de novo donor‐specific antibody (dnDSA) among HIR recipients categorized by age, race, or donor type. All received antithymocyte globulin (ATG) induction and triple maintenance immunosuppression. A total of 464 HIR recipients from 2007 to 2014 were reviewed. AR and dnDSA rates at 1 year for the entire population were 14% and 27%, respectively. AR ranged from 6.7% among living donor (LD) recipients to 30% in younger AA deceased donor (DD) recipients. De novo donor‐specific antibody at 1 year ranged from 7% in older non‐AA LD recipients to 32% in AAs. AA race remained as an independent risk factor for AR among DD recipients and for dnDSA among all HIR recipients. Development of both AR and dnDSA within the first year was associated with a 54% graft survival at 5 years and was an independent risk factor for graft loss. Despite utilization of recommended immunosuppression for HIR recipients, substantial disparities exist among subgroups, warranting further consideration of individualized immunosuppression in certain HIR subgroups.